Ikrar Sebagai Upaya Penanaman Nilai Agama dan Moral di Raudhatul Athfal (RA) Hj. Sri Musiyarti - Rhofiana, Alfina; Muslam, Muslam (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
The main thing for a person is belief as a guide to life. Confidence can be obtained through religious and moral education. The research objectives are: 1) Describing the pledge activities in the cultivation of religion and morals in RA Hj. Sri Musiyarti, 2). Knowing the inhibiting and supporting factors for the implementation of the pledge at RA Hj. Sri Musiyarti, 3). Knowing the effect of pledge activities in instilling religion and morals in RA Hj Sri Musiyarti. The research approach uses descriptive qualitative type. Data collection methods with observation, and documentation. The results showed that: 1) The implementation of the pledge at RA Hj. Sri Musiyarti is carried out every Monday-Thursday as an effort to instill religion and morals in children, 2). There are no inhibiting factors for the implementation of the pledge at RA Hj. Sri Musiyarti because the teacher plays a very important role in optimizing activities, 3). Pledge activities at RA Hj. Sri Musiyarti are proven to influence children to be able to believe in the pillars of faith and the pillars of Islam and to be able to say and memorize the shahada sentence, daily prayers, and short letters.